2018
DOI: 10.3390/ijerph15091837
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of BTEX in the Air of Tehran: A Systematic Review-Meta Analysis and Risk Assessment

Abstract: In the current study, the concentration of some pollutants which are categorized as volatile organic compounds (VOCs), including benzene (B), toluene (T), ethylbenzene (E), and o-xylenes (o-X), in the air of Tehran was evaluated by the aid of a systematic review and meta-analysis approach. Also, the health risk for the exposed population was estimated using the recommended methods by the Environmental Protection Agency (EPA). The rank order based on their concentration in BTEX was benzene (149.18 µg/m3: 31%) >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 77 publications
(115 reference statements)
0
18
0
1
Order By: Relevance
“…The HRI for nitrate exposure due to consumption was calculated using the Eq. (2) reported by previous investigations 43,44 (…”
Section: Health Risk Index (Hri)mentioning
confidence: 75%
“…The HRI for nitrate exposure due to consumption was calculated using the Eq. (2) reported by previous investigations 43,44 (…”
Section: Health Risk Index (Hri)mentioning
confidence: 75%
“…PAHs in the air and bound PM 2.5 have mutagenic and/or carcinogenic properties [13] and the metals include chromium (Cr), lead (Pb), arsenic (As), cadmium (Cd), nickel (Ni), manganese (Mn) and copper (Cu) bound with PM 2.5 induced to oxidative stress [14], following with an increase in DNA lesions [15].…”
Section: Methods Detailsmentioning
confidence: 99%
“…Carcinogenic risk (CR) of BTEX was calculated using the following equation (Abtahi et al, 2018; EPA, 2011; Zarandi et al, 2019):…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported the carcinogenic risks of benzene (Baghani et al, 2019). However, no evidence of mutagenicity and carcinogenicity for toluene, ethylbenzene, and xylene has been documented (Abtahi et al, 2018). Among workers, exposure to BTEX has demonstrated symptoms, such as headaches, cough, fatigue, eye irritation, nausea, dizziness, depression, and asthma (Alves et al, 2017; Cruz et al, 2017; Santiago et al, 2019).…”
Section: Introductionmentioning
confidence: 99%